2016
DOI: 10.1515/pomr-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Model of SO2 Scrubbing with Seawater Applied to Marine Engines

Abstract: The present paper proposes a CFD model to study sulphur dioxide (SO 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…With increasing the seawater alkalinity to not only improve the desulfurization efficiency but also weaken effects of SO 2 concentration and liquid–gas ratio, the explanation relies on the fact that a higher‐alkalinity seawater agent can provide a higher alkaline ion concentration to aid the SO 2 ‐absorption reactions consisting of SO 2 (aq) + H 2 O↔H + +HSO 3 − and H + +HCO 3 − ↔CO 2 (aq) + H 2 O . As the overall reaction rate accelerates, the SO 2 partial pressure in the liquid phase decreases, whereas that in the gas phase is maintained, resulting in the mass transfer driving force (i.e., the gap between the two partial pressures) increasing . In consequence, the desulfurization efficiency difference related to the liquid–gas ratio and SO 2 concentration is thus weakened.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing the seawater alkalinity to not only improve the desulfurization efficiency but also weaken effects of SO 2 concentration and liquid–gas ratio, the explanation relies on the fact that a higher‐alkalinity seawater agent can provide a higher alkaline ion concentration to aid the SO 2 ‐absorption reactions consisting of SO 2 (aq) + H 2 O↔H + +HSO 3 − and H + +HCO 3 − ↔CO 2 (aq) + H 2 O . As the overall reaction rate accelerates, the SO 2 partial pressure in the liquid phase decreases, whereas that in the gas phase is maintained, resulting in the mass transfer driving force (i.e., the gap between the two partial pressures) increasing . In consequence, the desulfurization efficiency difference related to the liquid–gas ratio and SO 2 concentration is thus weakened.…”
Section: Resultsmentioning
confidence: 99%
“…According to the absorbent used, wet scrubbers can be divided into open‐loop, closed‐loop, and hybrid systems. The open‐loop system utilizes the seawater's alkalinity to scrub SO 2 and emits the effluent into the sea after use . In this aspect, Han et al experimentally investigated the seawater desulfurization performance under laboratory conditions with a diesel engine exhaust used to represent ship exhaust and found that major seawater parameters such as the flow rate, alkalinity, and temperature significantly affected desulfurization .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, researchers had tackled problems pertinent to the spray scrubber applications, both on the experimental and modelling sides. The topic of sulfur dioxide absorption in liquid droplets has been investigated for some years now, from the atmospherical point of view and the simplified chemical models in the beginning [6], to the numerical modelling in the recent years [7]. Maurer [8] investigated the solubility, and the equilibrium concentrations of sulfur dioxide in water, Walcek and Pruppacher [6] studied the atmospherical absorption of SO 2 by clouds and raindrops, while Walcek et al [9] performed experiments on the freely falling droplets in rain shaft.…”
Section: Introductionmentioning
confidence: 99%
“…Wet scrubbers are divided into open‐loop, closed‐loop, and hybrid systems according to the used agent . The open‐loop system utilizes seawater to remove SO 2 and discharges the sulfur‐adsorbed waste liquid into sea after scrubbing . It has a low operation cost in the agent consumption (using the natural cheap seawater) but necessitates a larger scrubber space, because of a large seawater flux needed for scrubbing and simultaneously neutralizing the discharged liquid.…”
Section: Introductionmentioning
confidence: 99%